The Dual-Track Tuition Fee Model in Russia and Post-Soviet Countries - Smolentseva, Anna (International Higher Education, 2022)
The dual-track tuition fee model in post-Soviet countries is a distinctive funding model in international higher education. A legacy of the late Soviet state, which injected market mechanisms into the tuition fee-free socialist system, it divides students into two selection and funding streams regulated by different types of competition and price setting. This creates profound inequities, and, in most institutions, incentives to focus on revenue without regard for educational quality.